Magnetic resonance tomography capabilities and limitations in managing the efficacy of treatment with biological disease modifying anti-rheumatic drugs in ankylosing spondylitis - P. A. Shesternya; O. D. Gritsenko; P. A. Astanin; A. Yu. Stepanenko; N. V. Popov (Современная ревматология, 2021)
Extensive use of magnetic resonance imaging (MRI) in clinical practice revolutionized our understanding of the pathogenesis of axis spondyloarthritis (aSpA) and treatment approaches. The use of MRI to diagnose non-radiographic aSpA is well established. At the same time, the possibility of its use for follow-up and treatment assessment is actively discussed.Objective: To present comparative analysis of clinical and laboratory data, reflecting the activity of the disease, and analysis of MRI results in patients with ankylosing spondylitis (AS) receiving biological disease modifying anti-rheumatic drugs therapy (bDMARDs).Patients and methods. The study included 39 patients with AS, mainly men (74.3%), 24 patients (61.5%) had late and 15 (38.5%) – advanced stage of the disease. The average age was 41.0 [34.0; 48.0] years. All patients were administered bDNARDs; inhibitors of the tumor necrosis factor α or inhibitors of interleukin 17 were drug of choice. The median of treatment duration was 1.5 [1.0; 4,5] year. All patients had sacroiliac (SI) and spinal MRI. The activity of the disease was estimated using BASDAI and ASDAS-CRP/ESR indexes, functional disorders – using the BASFI questionnaire. Results and discussion. There was no significant difference in disease activity between patients with osteitis in the SI/spine or without it: BASDAI – 4.7 [2.7; 5,5] and 4.2 [2.9; 8,1], respectively (p=0.533); ASDAS-ESR – 2.6 [2.2; 3,0] and 2.6 [2.2; 3,2], respectively (p=0.725); ASDAS-CRP – 2.5 [2.1; 3,4] and 3.1 [2.8; 3.9], respectively (p=0.172). There was no significant difference in the number of osteitis foci between group of patients who have achieved the therapeutic target (ASDAS < 2.1) and those who have not (ASDAS ≥2.1) – 1.0 [0.0; 3.5] and 1.0 [1.0; 4.0], respectively, (p=0.376), and no difference in amount of inflammatory changes – 1.0 [0.2; 1.7] and 0.1 [0.0; 1,1] cm3, respectively (p=0.124). Conclusion. The data suggests a limited MRI informative value as a method for managing the efficacy of bDMARDs treatment in patients with the advanced / late stage of the AS.